Toward a molecular pathogenic pathway for Yersinia pestis YopM - Uittenbogaard, Annette M.; Chelvarajan, R. L.; Myers-Morales, Tanya; Gorman, Amanda A.; Brickey, W. J.; Ye, Zhan; Kaplan, Alan M.; Cohen, Donald A.; Ting, Jenny P.; Straley, Susan C. (Frontiers in Cellular and Infection Microbiology, 2012)
YopM is one of the six “effector Yops” of the human-pathogenic Yersinia, but its mechanism has not been defined. After delivery to J774A.1 monocyte-like cells, YopM can rapidly bind and activate the serine/threonine kinases RSK1 and PRK2. However, in infected mice, effects of Y. pestis YopM have been seen only after 24 to 48 h post infection (p.i.). To identify potential direct effects of YopM in vivo we tested for effects of YopM at 1h and 16-18h p.i. in mice infected systemically with 106 bacteria. At 16 h p.i., there was a robust host response to both parent and yopM-1 Y. pestis KIM5. Compared to cells from non-infected mice, CD11b+ cells from spleens of infected mice produced more than 100-fold greater IFN. In the corresponding sera there were more than 100-fold greater amounts of IFN, G-CSF, and CXCL9, as well as more than 10-fold greater amounts of IL-6, CXCL10, and CXCL1. The only YopM-related differences were slightly lower CXCL10 and IL-6 in sera from mice infected 16 h with parent compared to yopM-1 Y. pestis. Microarray analysis of the CD11b+ cells did not identify consistent transcriptional differences of > 4 fold at 18 h p.i. However, at 1 h p.i. mRNA for early growth response transcription factor 1 (Egr1) was decreased when YopM was present. Bone marrow-derived macrophages infected for 1 h also expressed lower Egr1 message when YopM was present. Infected J774A.1 cells showed greater expression of Egr1 at 1 h p.i. when YopM was present, but this pattern reversed at 3 h. At 6 h p.i., Cxcl10 mRNA was lower in parent-strain infected cells. We conclude that decreased Egr1 expression is a very early transcriptional effect of YopM and speculate that a pathway may exist from RSK1 through Egr1. These studies revealed novel early transcriptional effects of YopM but point to a time after 18 h of infection when critical transitional events lead to later major effects on cytokine gene transcription.